Biotransformation of capsaicin by Penicillium janthinellum AS 3.510. (March 2017) - Xin, Xiu-Lan; Wang, Yan; Fan, Guang-Jun; Chen, Liang; Sun, Cheng-Peng
Graphical abstract: Highlights: Four new metabolites2–5 were obtained from the biotransformation of capsaicin. P. janthinellum AS 3.510 was used to biotransform capsaicin. The Mo2 (OAc)4 -induced ECD method was used to determine the absolute configuration. This enzymatic reaction included hydroxylation, methylation, and epoxylation. Abstract: Biocatalysis of capsaicin (1 ) was performed by Penicillium janthinellum AS 3.510. Nine metabolites including four new compounds were afforded, and their structures were elucidated as (8 S )- trans -8-hydroxy-8-hydroxymethyl- N -vanillyl-6-nonenamide (2 ), 6-hydroxy-8-methyl- N -vanillyl-7-nonenamide (3 ), trans -8-methoxy-8-methyl- N -vanillyl-6-nonenamide (4 ), 6-methoxy-8-methyl- N -vanillyl-7-nonenamide (5 ), dihydrocapsaicin (6 ), ω -1-hydroxydihydrocapsaicin (7 ), ω -1-hydroxycapsaicin (8 ), ω -hydroxycapsaicin (9 ), N -(4-hydroxy-3-methoxybenzyl)-5-[3-(propan-2-yl)oxiran-2-yl]pentanamide (10 ) by 1D and 2D NMR and HRESIMS spectra. The biotransformation processes include hydroxylation, methylation, reduction, and epoxylation.